High temperature in potato: plant responses and adaptive cultivation strategies to increase production - Gultom, Siska Rahmayani; Hamdani, Jajang Sauman; Kusumiyati, Kusumiyati (Kultivasi, 2025)
Climate change, with global temperatures rising by 1.09°C from 1850–1900 to 2011–2020, threatens potato production, a critical staple crop, by exceeding the optimal temperature range of 15–20°C. This review synthesizes over 45 peer-reviewed studies published between 2015 and 2025 from Google Scholar and ScienceDirect to evaluate the physiological, morphological, and tuber quality responses of potatoes to high temperatures and to identify adaptive cultivation strategies for sustainable production. High temperatures reduce photosynthetic efficiency through chlorophyll degradation and stomatal closure, increase respiration, and divert photosynthates to vegetative growth, leading to 18–32% yield losses globally by the 2050s. Heat-tolerant varieties, such as Atlantic (11.47 tons/ha), Merbabu-17 (11.04 tons/ha), and Granola (3.61 tons/ha), maintain productivity in medium-altitude lands. Plant growth regulators (PGRs), including BAP, melatonin, and paclobutrazol, enhance tuber yield by regulating hormonal balance and antioxidant activity. Drip irrigation and mulching (e.g., straw, wheat, plastic films) improve water use efficiency and buffer soil temperature. These integrated strategies of heat-tolerant varieties, PGRs, irrigation, and mulching offer practical solutions to mitigate heat stress and ensure sustainable potato production under changing climate conditions.